CROSS BORDER LISTING AS MEANS OF AGRICULTURAL ENTERPRISE FINANCING - Popovych, Andriy (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
The international shares placement via IPO on the WSE by several Ukrainian companies, mainly from the sector of agricultural production and processing, makes an appealing case of relatively quick and inexpensive access to foreign borrowing markets. The WIG Ukraine index shows optimistic start, period of positive gains, dramatic fall at one point and significant volatility afterwards due to both the political and macroeconomic upheavals in the home country as well as internal problems of emitents. The comparison with other indexes of WSE and other exchanges reasonably suggests that the latter reason was the main cause of the deterioration of the indicator. The investigation on the parameters of the regression model that describe time series of WIG-Ukraine index with the help of the ARIMA model reveals that short-time predictions dominate investors decisions.